Multisensory processing in the auditory cortex - King, A; Hammond-Kenny, A; Nodal, F (Springer, 2019)
The capacity of the brain to combine and integrate information provided by the different sensory systems has a profound impact on perception and behavior. This is especially the case for audition, with many studies demonstrating that the ability of listeners to detect, discriminate, or localize sounds can be altered in the presence of other sensory cues. For example, the availability of congruent visual stimuli can make it easier to localize sounds or to understand speech, benefits that are most apparent when auditory signals are weak or degraded by the presence of background noise. Multisensory convergence has been demonstrated at most levels of the auditory pathway, from the cochlear nucleus to the auditory cortex. This is particularly the case in extralemniscal nuclei from the midbrain upward but has also been observed in the tonotopically organized lemniscal or core projections. In addition to inheriting multisensory signals from subcortical levels, the auditory cortex receives visual and somatosensory inputs from other cortical areas. Although nonauditory stimuli can evoke spiking activity in auditory cortex, they typically modulate auditory responses. These interactions appear to provide contextual cues that signal the presence of an upcoming sound, but they can also increase the information conveyed by cortical neurons about the location or identity of sounds and may even recalibrate cortical responses when the information provided by different sensory modalities is conflicting. Identifying the neural circuitry responsible for the behavioral consequences of multisensory integration remains an area of intense investigation.